The Representation of Struggle in the Poem 'Lā tantaẓir aḥadan fa-lan yaʾtī aḥad' by Faruq Juwaidah - Rangkuti, Hamzah Mahmudin; Abshar, Ulil; Hasaniyah, Nur (Maharaat: Jurnal Pendidikan Bahasa Arab, 2026)
The phenomenon of despair and the collapse of heroism in modern Arabic poetry represents a critical response to the socio-political stagnation of the post-Naksa era. This study aims to conduct a profound analysis of the poem " Lā tantaẓir aḥadan fa-lan yaʾtī aḥad" (Do Not Wait for Anyone, because nobody comes) by the renowned Egyptian poet Faruq Juwaidah, employing Michael Riffaterre's semiotic approach. As a central figure in contemporary romantic-realist poetry, Faruq Juwaidan utilizes the archetype of the "Knight" to critique the loss of agency in the Arab world. The research method is descriptive qualitative, applying Riffaterre's four analytical stages: heuristic and hermeneutic readings, analysis of indirect expression, determination of matrix and model, and hypogrammatic derivation. The findings reveal that the poem operates through a systematic displacement of meaning, where symbols of power (swords, horses) are inverted into signifiers of impotence. The matrix of the poem is identified as "the futility of external salvation," realized through the model of "The Deceived Knight." The study concludes that Faruq Juwaidah deconstructs the traditional Arab "Furusiyya" (chivalry) to manifest a bleak political allegory, urging a rupture from passive waiting. This research contributes to the understanding of how semiotic structures in poetry function as vehicles for ideological critique.